Pengaruh Konseling Behavioral Dengan Teknik Self Control Dalam Meminimalisir Perilaku Agresif Peserta Didik Kelas XI MIPA di SMA Negeri 4 Singaraja - Arnolda Zalshavira Diron; I Ketut Dharsana; Ni Ketut Suarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the effect of self-control technique behavioral counseling to minimize aggressive behavior in students. This study used a quasi-experimental design with nonequivalent post-test control group design. The population of this study were students of class XI SMA Negeri 4 Singaraja. The sampling technique used purposive sampling so that class XI MIPA 3 was obtained as the experimental class and class XI MIPA 2 as the control class. The data analysis method used is the t-test and effect size with the help of the SPSS for Windows program. The data collection instrument used observation and questionnaires regarding aggressive behavior. Based on the results of the analysis that has been carried out, the value of Sig. 0.000 <0.05 which means H0 is rejected. The results of the conclusion of this study are that behavioral counseling, self-control techniques have an influence on minimizing aggressive behavior in students.